2022
DOI: 10.3389/fenvs.2022.995990
|View full text |Cite
|
Sign up to set email alerts
|

Do regional government green innovation preferences promote industrial structure upgradation in China? Econometric assessment based on the environmental regulation threshold effect model

Abstract: China has been upgrading the industrial structure (ISU) at the regional level through innovation to achieve socioeconomic progress, but there is less known about the complex intermediary mechanisms regulating the government’s green innovation preference (GGIP)-ISU nexus from a regional perspective in China. Experts agree that varying environmental regulations (ER) intensity alters the relationship dynamics between innovation and ISU. Thus, using regional panel data (2005–2019), the paper develops an ER-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Based on the panel, our study found that both formal and informal environmental regulations could promote industrial structural upgrading, which was consistent with existing research findings [ 69 , 70 , 71 ]. In addition, we found that after science and technology innovation crosses a certain threshold, the interaction between informal environmental regulation and science and technology innovation is further enhanced, thus indirectly affecting the transformation and upgrading of industrial structure.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the panel, our study found that both formal and informal environmental regulations could promote industrial structural upgrading, which was consistent with existing research findings [ 69 , 70 , 71 ]. In addition, we found that after science and technology innovation crosses a certain threshold, the interaction between informal environmental regulation and science and technology innovation is further enhanced, thus indirectly affecting the transformation and upgrading of industrial structure.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Song et al [15] found a U-shaped relationship between ER and GI, indicating that as ER increases, its role will gradually change from suppressing to stimulating GI. Yang and Zhao [16], as well as Khattak [17], studied the impact of ER on GI and arrived at the same conclusion.…”
Section: Introductionmentioning
confidence: 61%
“…The core explanatory variable in this paper is the intensity of environmental regulation (ER) in each city. According to the existing literature, environmental regulation can be divided into formal regulation, which belongs to governmental actions, and informal regulation, which belongs to non-governmental organizations or individual actions [40]. In the current practice of environmental governance in China, the government still plays a dominant role, so the environmental regulation referred to in this paper focuses on the various environmental policies implemented by the government.…”
Section: The Core Explanatory Variablesmentioning
confidence: 99%